Implementasi Low Power pada Sistem Notifikasi untuk Gamer yang Bermain Intense Berbasis Embedded System - Irfan Pratomo Putra; Dahnial Syauqy; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In Indonesia, games have become a game that people love. Both from adults, teenagers, to children. Players in Indonesia have reached 43.7 million where 26% are people aged 21-35 years, then 21% of them are people aged 10 -20 years. If playing too long this can lead to a problem especially on their health. If they play the game for too long, then their eyes can feel sore, and otherwise can make headache caused by lack of room lighting. In addition to the problem of games there are also other problems, that problem is the resource they used. Therefore, there are systems that will provide notifications when gamers play unhealthy. Hopefully they can play in sufficient place of lighting, play within a safe distance from the monitor and prevent them from playing for too long. This system will be active continuously so it needs a lowpower method to suppress the use of resources, current, and the system can be active for as long as possible. The current that the system uses after testing is 3.8 mA in sleep state and when normally it's 169.9 mA. In addition to current testing, tested also how the level of accuracy of the sensor and obtained the accuracy of the distance sensor of 98.07% and then the accuracy of LDR sensor of 96.42%.